(untitled) - Cantù, Marco (San Francisco, Calif., 2005)
Mastering Borland Delphi 2005 is the best way to get up to speed, whether you're starting from scratch or have experience with an earlier version. Written by an award-winning and internationally known Delphi expert, this book shows you how to capitalize on Delphi's many advantages--including its clean language, speed of development, portability, and an active community that has produced hundreds of third-party tools.
Keywords: Computer software,Phần mềm máy tính; Development,Phát triển